Skrining Plasma Nutfah Jagung terhadap Kekeringan - Sri Gajatri Budiarti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
Most corn planted in marginal upland area which often experience drought. Early maturing and drought tolerant corn is needed for such environment. The objective of the experiment was to select genotype tolerant to drought. Experiment was conducted in Jakenan, Pati, Central Java during the dry season of year 2000. Split plot design was used, main plats consist of plant with drought and without drought strees. Subplots consist of 64 corn accessoris. Result of the experiment showed that based leaf rolling score (1.0), silk delay (1-3days), drought index greater than sensitive control (lkene 8149), 6 accessious were selected to be drought tolerant. Under drought condition, the 6 accessious yielded between 0.606 - 1.325 ton/ha and drought index between 0.73 - 0.92. Tolerant control (Wisanggeni) yielded 1.204 ton/ha and drought index 0.98 while sensitive control only 0.369 ton/ha. Days to harvest of the six accessious were between 71 - 85 days while the two control was 90 days.   Key words: Screening, Drought, Germ plasm, Maize